Impact of Intravenous Iron on Oxidative Stress and Mitochondrial Function in Experimental Chronic Kidney Disease - Faisal Nuhu; Anne-Marie Seymour; Sunil Bhandari (Antioxidants, 2019)
Background: Mitochondrial dysfunction is observed in chronic kidney disease (CKD). Iron deficiency anaemia (IDA), a common complication in CKD, is associated with poor clinical outcomes affecting mitochondrial function and exacerbating oxidative stress. Intravenous (iv) iron, that is used to treat anaemia, may lead to acute systemic oxidative stress. This study evaluated the impact of iv iron on mitochondrial function and oxidative stress. Methods: Uraemia was induced surgically in male Sprague-Dawley rats and studies were carried out 12 weeks later in two groups sham operated and uraemic (5/6 nephrectomy) rats not exposed to i.v. iron versus sham operated and uraemic rats with iv iron. Results: Induction of uraemia resulted in reduced iron availability (serum iron: 31.1 ± 1.8 versus 46.4 ± 1.4 µM), low total iron binding capacity (26.4 ± 0.7 versus 29.5 ± 0.8 µM), anaemia (haematocrit: 42.5 ± 3.0 versus 55.0 ± 3.0%), cardiac hypertrophy, reduced systemic glutathione peroxidase activity (1.12 ± 0.11 versus 1.48 ± 0.12 U/mL), tissue oxidative stress (oxidised glutathione: 0.50 ± 0.03 versus 0.36 ± 0.04 nmol/mg of tissue), renal mitochondrial dysfunction (proton/electron leak: 61.8 ± 8.0 versus 22.7 ± 5.77) and complex I respiration (134.6 ± 31.4 versus 267.6 ± 26.4 pmol/min/µg). Iron therapy had no effect on renal function and cardiac hypertrophy but improved anaemia and systemic glutathione peroxidase (GPx) activity. There was increased renal iron content and complex II and complex IV dysfunction. Conclusion: Iron therapy improved iron deficiency anaemia in CKD without significant impact on renal function or oxidant status.